New species and review of the Afrotropical clearwing moth genus Camaegeria Strand, 1914 (Lepidoptera: Sesiidae: Synanthedonini) - Bartsch, Daniel; Berg, Jutta (Zootaxa, 2012)
A review of the Afrotropical sesiid genus Camaegeria Strand, 1914 (Synanthedonini), which previously comprised onlya single species, C. auripicta Strand, 1914, is presented. Based on its genital morphology Camaegeria seems most closelyrelated to Episannina Aurivillius, 1905, which also occurs in Africa and is placed here in Synanthedonini. Differentialcharacters between Camaegeria, Episannina and the superficially similar Tipulamima Holland, 1893, are discussed. Sixspecies are transferred from other sesiid genera to Camaegeria: C. aristura (Meyrick, 1931) n. comb., C. exochiformis(Walker, 1856) n. comb., C. monogama (Meyrick, 1932) n. comb., C. sophax (Druce, 1899) n. comb., C. sylvestralis(Viette, [1955]) n. comb. and C. xanthopimplaeformis (Viette, [1955]) n. comb. One new species, Camaegeria massai n.sp. is described from eastern Africa and four new species, C. lychnitis, C. polytelis, C. viettei and C. xanthomos n. spp.are described from Madagascar. New junior synonyms of Camaegeria aristura are Aegeria leptomorpha Meyrick, 1931n. syn. and Aegeria hadassa Meyrick, 1932 n. syn., and a new junior synonym of C. monogama is Macrotarsipus lioscelis Meyrick, 1935 n. syn.